Pain Assessment Following Open Hemorrhoidectomy Under Local Anesthesia Versus Saddle Block: A Multicenter Randomized Controlled Trial. - Sikakulya, Franck Katembo; Ssebuufu, Robinson; Okedi, Xaviour Francis; Baluku, Moris; Lule, Herman; Kiyaka, Sonye Magugu; Kyamanywa, Patrick (Kabale University, 2024)
Background There is a disparity in evidence on pain assessment post open hemorrhoidectomy (OH) using local anes- Thesia and its use in developing countries are different from those in developed countries. Therefore, we conducted this study to assess the occurrence of postoperative pain following open hemorrhoidectomy under local anesthesia versus saddle block for uncomplicated 3rd or 4th-degree hemorrhoids. Methods This was a prospective equivalence randomized, double-blind controlled trial conducted from December 2021 to May 2022 among patients with primary uncomplicated 3rd or 4th-degree hemorrhoids. Pain severity was assessed at 2, 4 and 6 h post open hemorrhoidectomy using visual analogue scale (VAS). Data was analyzed using SPSS version 26 at a p<0.05 as statically significant using the visual analog scale (VAS). Results We recruited 58 participants in this study who underwent open hemorrhoidectomy under local anesthesia or saddle block (29 participants per group). The sex ratio was of 1.15 of female to male and a mean age of 39±13. VAS was found to be different at 2 h post-OH compared to other times of pain assessment but not statically significantly by area under the cover (AUC) (95% CI=486–0.773: AUC=0.63; p=0.09) with a significance by Kruskal–Wallis’s test (p:0.925). Conclusion Local anesthesia was found to have a similar pain severity occurrence in the post-operative period among patients undergoing open hemorrhoidectomy for primary uncomplicated 3rd or 4th-degree hemorrhoids. Close monitoring of pain in the postoperative period is mandatory especially at 2 h to assess the need of analgesia. Trial registration Pan African Clinical Trials Registry, PACTR202110667430356. Registered on 8th October, 2021.